Fermentation Pattern of Infant Formulas Containing Different Prebiotics. Issue 5 (May 2015) - Vanderhoof, Jon; Ferguson, Paul; Pauley-Hunter, Rosemary; Prestridge, Laurel
Abstract : Abstract: Prebiotics play a role in the development of intestinal flora. When exposed to unabsorbed food, such as prebiotic carbohydrates, intestinal bacteria produce hydrogen. Increases in hydrogen may signify a slower rate of fermentation or digestion. In this blinded, crossover study, infants (n = 13) consumed formula containing either 4 g/L galactooligosaccharide (GOS) or 4 g/L polydextrose (PDX) + GOS, and breath hydrogen was measured. Breath hydrogen was higher in the PDX/GOS group versus GOS alone (mean ± standard error, 25.35 ± 2.87 ppm vs 13.69 ± 2.87 ppm, P  = 0.0001). These results indicate that the formula with PDX/GOS may have undergone slower digestion.